Spatial and diachronic challenges encountering literary Arabic translators of the classical Arabic Literature into English - Almohish, Nouf Rashed Ibrahim (Research Journal in Advanced Humanities, 2024)
This research endeavors to shed light on the challenges that are associated with translating traditional Arabic literary works which impedes modern readers from understanding and grasping the content of these papers. The research utilized a diversified methodology, which included the application of a number of various translation techniques and linguistic methodologies, in order to investigate the influence that geography and time have had on the translation of classic Arabic literature. This was done in order to investigate the influence that time and space have had on the translation of those works. The research has resulted in the discovery of a considerable number of findings. The fact that classical Arabic literature is going through a semantic shift is one of the most crucial things that is taking place. This is a result of the fact that a number of lexical items have been subjected to semantic alterations, which can either be ameliorative or pejorative to the language. The translator has a propensity to encourage the recipient to engage with ancient literature from a contemporary perspective, which may make it more difficult to arrive at an interpretation of the text that is more accurate. This is another important outcome that can occur.